Pengaruh Format Soal Dalam Bentuk Animasi Terhadap Validitas Dan Reliabilitas Tes Pemahaman Konsep Pembiasan Cahaya - Suhandi, Andi; Samsudin, Achmad; Setyawan, Agus (BERKALA FISIKA, 2010)
This research was conducted to investigate the influence of question format in the form of animation to the validity and reliability tests of understanding the concept of light refraction. For the sake of it has constructed a test of understanding the concept of the refraction of light in an animation format by replacing static pictures and descriptions of the phenomenon of refraction of light propagation in a static format (paper and pencil test) with computer animation. Second test version, the version animated and static versions then tested to 100 students from three high schools in Bandung, which has received the learning material of light refraction. The second test version of the test results are then analyzed to determine the validity and reliability respectively. To see the influence of a test version of the level of validity and reliability, then compare the level of validity and reliability of both versions of this test. The results showed that both the level of validity and reliability tests in levels higher than the animated version of the test in the static version. Level of validity for the second consecutive test version 0.89 (very high) for an animated version and 0.71 (high) for the static version, whereas the level of reliability, 0.92 (very high) for an animated version and 0.78 (high ) for the static version. These results show obvious evidence of the influence of question format in the form of animation on the level of validity and reliability tests of understanding the concept of habituation of light. Keywords: Animation Test Version, Test Version Static, validity, reliability, refraction of light